Uso da sintaxe espacial para delimitação de espaço compartilhado no centro de Fortaleza - Cruz, Gizelle Heléne Jerônimo da (2019)
Given the perspective of urban interventions in the city of Fortaleza, it is necessary to evaluate and promote new proposals aimed at making living experiences safer and more efficient travel. The concept of shared space is used as a way to meet the requirements of comfort and safety, since thus the priority of non-motorized modes is ensured, making the demand for motor vehicles on the road secondary. With this in mind, this paper seeks to contribute in order to make a qualitative analysis of the proposal to implement a shared space in historical centers, suggesting accessibility and mobility indicators capable of providing parameters for the adoption of public policies that improve transportation services. public and walkability. Through space syntax, obtaining configurational characteristics of the Center's road network – such as integration and connectivity, this work seeks to validate a pedestrian zone that optimizes the movement of people in this region, promoting more comfort and safety. Some modes of transport are analyzed with data beyond the spatial syntax to compare the existing situation with the proposed situation according to the zone delimitation. From the configurational variables obtained from the spatial syntax analysis, it is possible to identify candidate pathways for circulation in specific ways, thus determining a suitable region for the implementation of a shared space that mainly facilitates pedestrian displacements. NOME: